Associations between smartphone use and mental disorders in college students: a systematic review - Santos, Renata Maria Silva; Oliveira, Gabriela Bahia de; Fernandes, Fernanda Martins; Ventura, Samara de Alcântara; Romano-Silva, Marco Aurélio; Miranda, Debora Marques de (International Journal of Research in Medical Sciences, 2024)
Smartphones are now ubiquitous in the daily lives of undergraduate students, but their excessive use may be related to psychological problems and to the development of mental disorders. To verify the influence of smartphone use on the development of mental disorders in university students, a systematic review of the literature was conducted, according to preferred reporting items for systematic reviews and meta-analysis (PRISMA) and registered in PROSPERO under number CRD42023401060. The search was carried out in June 2024 with the descriptors: “smartphone”, “university students”, “college students” and “mental disorders”, in the PubMed, PsycInfo and Scopus databases. Of the 48 studies included, most found associations between excessive use of smartphones and the presence of mental disorders in university students. Only two articles observed improvement in anxiety, depression and stress associated with smartphone use and one study found no associations. Depression, anxiety, and stress were the main mental disorders found among university students. The excessive use of smartphones is associated with the presence of psychological problems in university students. Constant smartphone availability and online studies favours the development of psychopathologies in university students. The findings in this review strengthen the evidence of the need to develop strategies to live in a healthy way with the digital world.